WATER POWER GENERATOR FOR PUBLIC ROAD ILLUMINATION LIGHTS OF PADI VILLAGE MOJOKERTO - Akhmad solikin; Rohib Ilma Suktawan (BEST, 2020)
Electricity problems in rural areas more and more electric power is needed. Until now, power plants that use water turbines are environmentally friendly electricity producers, so the potential for energy from the air needs to be utilized to address the demand for electricity. Therefore, the solution to this problem is to use the "Design and Construction of Hydroelectric Generator for Public Street Lighting". The generator is a source of electric voltage obtained by converting mechanical energy into electrical energy. The generator works based on the principle of electromagnetic induction, which is by rotating a coil in a magnetic field so that the induced GGL (Electric Motion Force) arises. In this thesis, a research is conducted on the Water Turbine Generator in the river in the village area of Padi Gondang Mojokerto as an object of water flow in order to generate electric power to reduce crime in the area in the form of a load object in the form of Public Street Lighting.